Continuum of care for maternal and newborn health services in Nepal: An analysis from demographic and health survey 2022 - Achyut Raj Pandey; Bikram Adhikari; Raj Kumar Sangroula; Parash Mani Sapkota; Shophika Regmi; Shreeman Sharma; Bishnu Dulal; Bipul Lamichhane; Saugat Pratap KC; Pratistha Dhakal; Sushil Chandra Baral (PLoS ONE, 2025)
Introduction With high burden of maternal mortality and stagnant neonatal mortality, maternal and newborn health services have remained a priority program for Nepal. This study aims to assess the determinants of four or more antenatal care (≥4 ANC) visits, institutional delivery (ID), postnatal care (PNC) visit for mother and newborn within the first two days of delivery and the continuum of care. Methods We performed weighted analysis of Nepal Demographic and Health Survey (NDHS) 2022 data accounting for complex survey design. The NDHS is a nationally representative cross-sectional survey that employs a two-stage stratified sampling technique to select participants. We analyzed data from 1,891 women who had live births within two years prior to the survey. Distribution of variables are described using frequency, percentage, and 95% confidence intervals (CI). We performed bivariate and multivariable logistic regression and the results are presented in crude odds ratio (COR), adjusted odds ratio (AOR) and 95% CI. Results In the study, 80.62% (95% CI: 77.95, 83.03) of participants had ≥ 4 ANC visits, 79.37% (95% CI: 76.68, 81.82) had ID, and 62.56% (95% CI: 56.67, 65.36) received PNC for mother and newborn within two days of delivery. Likewise, 67.59% (95% CI: 64.59, 70.45) had both ≥ 4 ANC visits and ID, while 51.01% (95% CI: 48.08, 53.93) had all three components of the continuum of care: ≥ 4 ANC visits, ID, and PNC visit within two days of delivery. The richest wealth quintile participants had three folds higher odds (AOR: 2.98, 95% CI: 1.83, 4.83) of completing continuum of care, while the odds were two folds (AOR: 2.04, 95% CI: 1.41, 2.94) higher for richer wealth quintile participants. Participants with birth order three or more had lower odds (AOR: 0.50, 95% CI: 0.36, 0.69) of completing all three continuum of care components. Among other variables associated with continuum of care were province, distance to facility and internet use. Conclusion Significant disparities exist in continuum of care or its components based on wealth quintile, province, and place of residence. Tackling economic gaps, provincial disparities, and leveraging technology are crucial for ensuring fair access to essential maternal health services. Nepal’s transition to a federal structure with 7 provinces and 753 local governments with decision making authority presents an opportunity to test and scale up innovative strategies for improving continuum of care coverage.